Unicity of Meromorphic Solutions of the Pielou Logistic Equation - Sheng Li; Baoqin Chen (Discrete Dynamics in Nature and Society)
This paper mainly considers the unicity of meromorphic solutions of the Pielou logistic equation yz+1=Rzyz/Qz+Pzyz, where Pz,Qz, and Rz are nonzero polynomials. It shows that the finite order transcendental meromorphic solution of the Pielou logistic equation is mainly determined by its poles and 1-value points. Examples are given for the sharpness of our result.